1. The problem statement, all variables and given/known data Mass 1 (2.77 kg) moves with an initial velocity (1i - 1j) and mass 2 (1 kg) starts at rest. After the collision, M2 moves with a velocity of (2i - 3j). What is the final velocity of m1? 2. Relevant equations Since they don't stick together, KE and linear momentum are conserved. M1V1ix + M2V2ix = M1V1fx + M2V2fx M1V1iy + M2V2iy = M1V1fy + M2V2fy 1/2 M1V1i^2 + 1/2M2V2i^2 = 1/2 M1V1f^2 + 1/2M2V2f^2 V1f = (sqrt)V1xf^2 + V1yf^2 3. The attempt at a solution I don't really understand these problems, and we had a substitute professor in to teach this, so here goes nothing, literally. 2.77 (1) + 0 = 2.77 Vx + 1(2) Vx = 0.278 m/s ???? 2.77(-1) + 0 = 2.77 Vy + 1(-3) Vy = 0.0.83 m/s ????? This doesn't seem right? Shouldn't I need to use th equations for KE for an elastic collision?